A literature review of benson relaxation technique for reducing anxiety in patients with chronic kidney disease - Mardiah, Adriana; Widodo, Arif; Thuy, Luu Thi (Innovation in Health for Society, 2022)
Hemodialysis is cleaning blood through an artificial kidney or dialyzer assisted by a machine. Kidney failure patients undergoing therapy experience anxiety due to various stressors. One way to overcome fear is to use relaxation therapy, including Benson relaxation. Benson relaxation is a breathing relaxation technique with the addition of an element of belief in the form of words that express the anxiety that the patient is experiencing. This literature aims to determine the effectiveness of Benson's relaxation on reducing stress in chronic kidney failure patients undergoing hemodialysis. A literature review comparing some literature through the journal databases used is Pubmed, Google Scholar, ScienceDirect, Garuda Portal, and Jane Semantic. The keywords are "Benson relaxation, anxiety, chronic renal failure and hemodialysis," "Benson relaxation technique on the anxiety of patient hemodialysis," "Benson relaxation for anxiety disorders," or "Benson relaxation for patients undergoing hemodialysis" or "non-pharmacological therapy for reduce anxiety from 2016-2021 full text. There are seven journals reviewed and used in this literature review. The results show that Benson relaxation is proven effective in reducing anxiety in chronic kidney failure patients undergoing hemodialysis. Keywords: Kidney disease; nursing care; relaxation technique; anxiety; psychological outcomes